2022
DOI: 10.4102/safp.v64i1.5434
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing treatment adherence in hypertension and HIV management in South Africa: A comparative literature review

Abstract: Methods: A comprehensive literature review was carried out. PubMed, ScienceDirect, Cochrane and Embase were searched for English publications between 2000 and 2021.Results: A total of 50 articles covering quantitative and qualitative studies were included. Many studies identified poor adherence levels to antihypertensive treatment, reaching a substandard adherence rate of 41.9%, whilst most studies on the HIV-positive population reported good levels of adherence, with adherence rates of more than 90%. Being of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The South African National Department of Health has made asserted efforts in improving the state of preventative healthcare by reengineering the primary healthcare model to be integrated in the district health system, with greater emphasis on the delivery of community-based services and a focus on the social determinants of health thus improving access to basic healthcare services significantly. 38 Notwithstanding this, adherence to treatment regimens is generally low, 39 , 40 which complicates chronic healthcare and prevention in the country.…”
Section: Resultsmentioning
confidence: 99%
“…The South African National Department of Health has made asserted efforts in improving the state of preventative healthcare by reengineering the primary healthcare model to be integrated in the district health system, with greater emphasis on the delivery of community-based services and a focus on the social determinants of health thus improving access to basic healthcare services significantly. 38 Notwithstanding this, adherence to treatment regimens is generally low, 39 , 40 which complicates chronic healthcare and prevention in the country.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, most of the chronic patients in South Africa use PHC facilities for primary care treatment accessed through the Centralised Chronic Medicine Dispensing and Distribution Programme (CCMDD), and adherence to the treatment of single conditions is suboptimal, except for HIV [ 13 , 65 , 95 ]. The World Health Organization (WHO) calls for universal health insurance and health service coverage in LMICs, particularly for vulnerable groups [ 96 ], as well as the United Nations (UN)’ sustainable development goals (SDG) 3 on Good Health and Well-Being to ensure healthy lives and promote well-being for all at all ages [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, research published in the "Nigerian Journal of Clinical Practice" found that adherence rates among hypertensive patients ranged from 23% to 69%, with a considerable proportion of nonadherent individuals (Akintunde, 2015). In South Africa, a study published in the "South African Medical Journal" reported that only 27% of hypertensive patients were adherent to their prescribed medications (Enslin, 2022).…”
Section: Empirical Literature 21 Prevalence Of Adherence To Anti-hype...mentioning
confidence: 99%
“…Poor adherence, influenced by various factors such as health literacy, cost, cultural beliefs, and provider-patient relationships, contributes to inadequate treatment, potentially leading to complications (James, 2014). Additional factors include comorbidities, medication changes, side effects, and dosage variations (Enslin, 2022;Weldegebreal, 2019;Agbor, 2018;Ferdinand, 2017).…”
Section: Introductionmentioning
confidence: 99%